2016
DOI: 10.1093/mnrasl/slw043
|View full text |Cite
|
Sign up to set email alerts
|

Could multiple voids explain the cosmic microwave background Cold Spot anomaly?

Abstract: Understanding the observed Cold Spot (CS) (temperature of ∼ −150µK at its centre) on the Cosmic Microwave Background (CMB) is an outstanding problem. Explanations vary from assuming it is just a 3σ primordial Gaussian fluctuation to the imprint of a supervoid via the Integrated Sachs-Wolfe and Rees-Sciama (ISW+RS) effects. Since single spherical supervoids cannot account for the full profile, the ISW+RS of multiple line-of-sight voids is studied here to mimic the structure of the cosmic web. Two structure conf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…Firstly, our results provide a framework to re-think the qualitatively similar case of the CMB Cold Spot (see e.g. Cruz et al 2005;Finelli et al 2015;Szapudi et al 2015;Kovács & García-Bellido 2016;Naidoo et al 2016Naidoo et al , 2017. With a significant enhancement of the density-temperature correlation at large scales, the Cold Spot and the Eridanus supervoid can plausibly be related via this unexpected excess signal.…”
Section: Discussionsupporting
confidence: 58%
“…Firstly, our results provide a framework to re-think the qualitatively similar case of the CMB Cold Spot (see e.g. Cruz et al 2005;Finelli et al 2015;Szapudi et al 2015;Kovács & García-Bellido 2016;Naidoo et al 2016Naidoo et al , 2017. With a significant enhancement of the density-temperature correlation at large scales, the Cold Spot and the Eridanus supervoid can plausibly be related via this unexpected excess signal.…”
Section: Discussionsupporting
confidence: 58%
“…One could argue that the alignment of the CMB Cold Spot and the large z = 0.14 void implies a causal link though the improbability of alignment but voids of this scale are not expected to be unique (Nadathur et al 2014, Kovács et al Table 3 have been summed and the result fitted to eq. (3) of Naidoo et al (2016). The shaded region (light blue) is the 68% confidence interval from the coldest spots identified in Gaussian simulations (see Nadathur et al 2014, Fig 6).…”
Section: Origin Of the Cmb Cold Spotmentioning
confidence: 96%
“…In the version of Planck Collaboration et al (2016b), it was found that the temperature profile of the Cold Spot was poorly described by the simulations with < 1 − 2% having a higher χ 2 compared to the mean than the data. Here we shall essentially adopt this approach, now following Nadathur et al (2014) and Naidoo et al (2016), and ultimately test how much any foreground void that is found can reduce this 1-2% significance assuming the original SMHW kernel.…”
Section: Decmentioning
confidence: 99%
“…On the other hand, large-scale structures can also generate it. The anomaly can be explained by the linear/non-linear integrated Sachs-Wolfe ⋆ E-mail: yhiguchi@asiaa.sinica.edu.tw (ISW) effect or the Rees-Sciama (RS) effect (Rees & Sciama 1968) caused by a supervoid with a radius of 200−300h −1 Mpc in the local Universe (Inoue & Silk 2006Sakai & Inoue 2008;Tomita & Inoue 2008;Inoue et al 2010) or multiple voids (Naidoo et al 2016). However, the probability of having such a large void is low in the ΛCDM model and multiple voids cannot explain the feature of a hot ring around the Cold Spot.…”
Section: Introductionmentioning
confidence: 99%